Dreams Deferred: The Concept of the US-Mexican Borderlands between the Global North and the South - Šesnić, Jelena (2011)
On the example of T. C. Boyle's novel _The Tortilla Curtain_ (1995), Karen Tei Yamashita's novel _Tropic of Orange_ (1997), and the US-Mexican feature film _Sleep Dealer_ (2008) by Alex Rivera, it is argued that a new conceptualization of the US-Mexican border arises. The new idea of the border is immersed in globalization, departs form the earlier model of the borderlands, and is attuned to newer forms of political, social and cultural restructuring between the North and the South. Concepts that help account for the recent developments are the "immigration shock", the biopolitics of immigration into the USA, and a new form of sovereignty in a globalized world.
Projekt MZOS
ENG